2019
DOI: 10.1097/j.pain.0000000000001682
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter systems involved in placebo and nocebo effects in healthy participants and patients with chronic pain: a systematic review

Abstract: The investigation of neurotransmitter systems in placebo and nocebo effects has improved our understanding of these phenomena. Yet, most studies involve healthy participants. Because the pain modulatory system may differ in healthy participants and patients with chronic pain, it is important to investigate the evidence for neurotransmitter involvement in placebo and nocebo effects in each of these populations. PubMed, Embase, and Scopus databases, and the Cochrane Library were searched for articles investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 66 publications
2
24
0
1
Order By: Relevance
“…However, acute pain in healthy participants is not an appropriate surrogate for chronic pain, given that patients with chronic pain are characterized by significant changes in their underlying neuroanatomical structural volumes as well as functional brain connectivity 505152. Furthermore, placebo treatments in chronic pain engage neurotransmitters that are distinct from those engaged by acute pain experienced in the laboratory 53. Nevertheless, acute pain experiments provide important proof of concept findings elucidating placebo effects.…”
Section: Evidence For Theories Of Placebo Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, acute pain in healthy participants is not an appropriate surrogate for chronic pain, given that patients with chronic pain are characterized by significant changes in their underlying neuroanatomical structural volumes as well as functional brain connectivity 505152. Furthermore, placebo treatments in chronic pain engage neurotransmitters that are distinct from those engaged by acute pain experienced in the laboratory 53. Nevertheless, acute pain experiments provide important proof of concept findings elucidating placebo effects.…”
Section: Evidence For Theories Of Placebo Effectsmentioning
confidence: 99%
“…This maladaptive positive feedback loop relies on internal top-down predictions that are now relatively divorced from sensory feedback (fig 5). Because of these pathophysiological differences, not surprisingly, evidence suggests that the “chronic pain brain,” compared with the brains of healthy volunteers in acute pain experiments, also responds to placebos through a different set of neurotransmitters and neuroanatomical substrates 5053125…”
Section: Evidence For Theories Of Placebo Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the effects of different sham stimulations on neural networks need to be further investigated, a placebo effect might be involved if those sham stimulations are experienced differently on the scalp. Studies examining whether chronic pain populations, including FMS, are more responsive to placebo than non-pain healthy controls show mixed findings [59][60][61] ; however, a systematic review investigating placebo-intervention against notreatment comparator groups in FMS found that the magnitude of placebo effects increases with the effect size of the active treatment 62 . While it is possible that a higher intensity sham stimulation would give rise to a stronger placebo response, we observed no significant differences in participants' guesses as to whether they received sham or active treatment between either sham group nor the active group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a blood sample will be taken at screening visit in order to identify COMT polymorphisms by PCR analysis. In addition, (1) treatment expectation will be assessed by the Treatment Expectation Questionnaire (TEX-Q 42 ), which distinguished between symptomspecific effects and effects related to quality of life and functional capability; (2) fear of pain by the Fear of Pain Questionnaire 43 ; (3) pain catastrophising by the Pain Catastrophizing Scale, 44 as these personality traits have been shown to be positively related to subjective pain intensity and fear of pain has further been shown to be the most robust predictor of pain chronification [45][46][47] ; (4) personality traits using the Behavioral Inhibition and Approach System [48][49][50] and the Short Version of the Big Five Inventory 51 due to the close link between personality traits associated to dopamine release, reward processing and expectation effects of treatment outcome 52 ; (5) anxiety and depression by the State-Trait Anxiety Depression Inventory 53 and stress by the Perceived Stress Scale 54 as depression, anxiety and psychological distress have been reported to be susceptible to modulation through OLP treatment 7 55 ; and (6) somatisation by the Somatosensory Amplification Scale 56 as a predictive role of somatosensory amplification in the development of side effects or negative expectation effects has been observed. 41 54 57 Further, a questionnaire (Generic Rating for Treatment Pre-experiences, Treatment Expectations, and Treatment…”
Section: Recruitmentmentioning
confidence: 99%